A Traumatic Direct Inguinal Hernia from Pelvic Ring Disruption. (10th July 2018) - Chow, Kevin L.; Smith-Singares, Eduardo; Doherty, James
Abstract : Introduction . Pelvic fractures usually involve a high-energy traumatic mechanism and account for approximately 3% of all blunt traumatic skeletal injuries. Additional musculoskeletal injuries are found in over 80% of unstable pelvic fractures. Traumatic abdominal wall hernias (TAWHs) are a rare entity, and traumatic inguinal hernias (TIHs) associated with open-book pelvic fractures have not been described previously. Case Presentation . We present the case of a 45-year-old male motorcyclist involved in a collision resulting in a traumatic direct inguinal hernia due to abdominal wall disruption from an open-book pelvic fracture. He underwent a combined operation with an open reduction and internal fixation (ORIF) of his pelvic fracture and an abdominal wall reconstruction with a modified Stoppa technique utilizing mesh for his hernia. Discussion . This is a unique presentation of a TIH due to an open-book pelvic fracture after blunt abdominal trauma. The formation of TAWH is typically from a combination of local tangential shearing forces and a sudden rise in intraabdominal pressures damaging the muscle, fascia, and peritoneum while the skin remains intact. In patients without hollow viscous injuries and gross contamination, these hernias can be repaired safely with mesh in the acute setting simultaneously with pelvic reduction.